EFEKTIVITAS PELAYANAN “OPEN TABLE” DI PERUSAHAAN DAERAH AIR MINUM (PDAM) SURYA SEMBADA KOTA SURABAYA - Larasati Novia Rinita; Tukiman Tukiman (Jurnal Penelitian Administrasi Publik, 2019)
Based on the Decree of the Directors of Surabaya City PDAM Surya Sembada No. 12 of 2018 On 10 January 2018, PDAM Surya Sembada City of Surabaya realized a service innovation, namely Open Table Services. The purpose of this study was to describe and analyze the effectiveness of open table services at the Surya Sembada Regional Drinking Water Company (PDAM) in Surabaya using qualitative research methods with observation data collection techniques, interviews and documentation, and data analysis by data collection, data condensation, presentation. data, and drawing conclusions. The location of this research is at Siola Public Service Mall, PDAM Basuki Rahmat Water House, and Mobile Service Car. The research results obtained are: (1) Resources, funds, facilities and infrastructure that can be used are effective but not maximized. (2) The quantity and quality of services produced are effective. (3) The time limit for producing goods or services is effective. (4) The procedures that must be followed are already effective. Keywords: Effectiveness, Open Table Service